The Community Satisfaction and Participation of the Health Planning Process in Primary Health Care - Sriatmi, Ayun; Fatmasari, Yunila (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
PHC as a public service institution is obliged to comply with the public service standard regarding with the community participatory principle. This research aimed to describe the community satisfaction and participation level in the PHC planning. Descriptive qualitative with 14 informants from 4 PHC in districts of Semarang and Kudus. Data were collected by indepth interview and analyzed with content analysis. Communities are satisfied with the PHC service because of the good service and uncomplicated procedure, which has impact to increase the daily visits. This situation makes queue time longer and the fatigue level of the officer tends to decrease the satisfaction. Communities have been involved in the planning mechanism, although only limited to the situational analysis phase. The Health Office is expected to facilitate the addition of PHC personnel and PHC also have to fulfill the need of human resources through the plans that have been done.Ã‚Â